Iowa Birdline update, December 28, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for December 28, 1992. The highlights for the update include sightings of a Snowy Owl, Townsend's Solitaire and four Yellow-rumped Warblers. Also included are handwritten notes with sightings of two Northern Saw-whet Owls, two Trumpeter Swans and a White-winged Crossbill. Epson - sheet feed/flatbed